Effective population sizes of a major vector of human diseases, Aedes aegypti. (3rd September 2017) - Saarman, Norah P.; Gloria‐Soria, Andrea; Anderson, Eric C.; Evans, Benjamin R.; Pless, Evlyn; Cosme, Luciano V.; Gonzalez‐Acosta, Cassandra; Kamgang, Basile; Wesson, Dawn M.; Powell, Jeffrey R.
Abstract: The effective population size ( N e ) is a fundamental parameter in population genetics that determines the relative strength of selection and random genetic drift, the effect of migration, levels of inbreeding, and linkage disequilibrium. In many cases where it has been estimated in animals, N e is on the order of 10%–20% of the census size. In this study, we use 12 microsatellite markers and 14, 888 single nucleotide polymorphisms (SNPs) to empirically estimate N e in Aedes aegypti, the major vector of yellow fever, dengue, chikungunya, and Zika viruses. We used the method of temporal sampling to estimate N e on a global dataset made up of 46 samples of Ae. aegypti that included multiple time points from 17 widely distributed geographic localities. Our N e estimates for Ae. aegypti fell within a broad range (~25–3, 000) and averaged between 400 and 600 across all localities and time points sampled. Adult census size (Nc ) estimates for this species range between one and five thousand, so the N e / N c ratio is about the same as for most animals. These N e values are lower than estimates available for other insects and have important implications for the design of genetic control strategies to reduce the impact of this species of mosquito on human health.